Étudier à distance en contexte de pandémie : qu'en dit le premier cycle universitaire ? - Perrine Martin; Christine Félix; Sophie Gebeil (Recherches en Éducation)
On 30 October 2020, in the context of a pandemic and a second period of confinement, French stu-dents were forced to follow distance learning. This article focuses on the effects of this new distance learning organization on the work and educational activity of French first-year university students from different disciplinary sectors and aims to contribute to a better understanding of their practices based on what students say they did to carry out their work. Moreover, by focusing on the analysis of the students' experiences through a comprehensive and critical look at distance learning, this research intends to contribute to a better understanding of the students' study conditions and therefore of their success regarding their profile as much in terms of their material learning conditions as in terms of their disciplinary sector of study.